Naila Kabeer, Geetha B. Nambissan, and Ramya Subrahmanian. Child Labour and the Right to Education in South Asia: Needs versus Rights? New Delhi: Sage Publications, 2003. 412 pages. Paperback. Indian Rs 365.00. (The Pakistan Development Review, 2003)
The volume is based on the proceedings of a workshop, organised on the issue of child labour and the right to education. The studies in the volume reflect on topics related to the problems of universalising education in South Asia. All the studies are based on the experience of either Bangladesh or India, with the exception of one or two studies where a comparison with other South Asian countries is considered. The problem of child labour is quite widespread in South Asia and that has prevented children in these societies from participating in schooling. At the same time, there are children who are neither at school nor at work. The reason identified for this is not only poverty but also the school system, as well as discrimination on the basis of caste, gender, tribal, or religious reasons. The volume generally examines the patterns of social discrimination and how this problem has been aggravated by the formal educational system. It also reflects on policy interventions addressing the problem—the efforts by the government, on the one hand, and by the non-governmental organisations, on the other.